Liberalization of Trade in Financial Services : Lessons from Latin America and the Caribbean - Stephanou, Constantinos (2012)
This policy note is based on a project on financial services and trade agreements in the Latin America and Caribbean Region. It emphasizes that the liberalization of trade in financial services is helpful to, but is not a panacea for, domestic financial system modernization. It adds that the means of liberalizing trade in financial services may also determine the extent of the benefits that can be attained and that any trade commitments in financial services will need to be aligned with China's financial system condition and policy objectives. The author points out however, that China can also draw useful policy lessons from the Latin America and Caribbean (LCR) experience when negotiating financial services in Preferential Trade Arrangement (PTAs) by firstly, the inclusion of financial services which depends greatly on the existence of offensive interests and of asymmetric bargaining powers between the negotiating counterparts; secondly, the case studies which strongly indicate the importance of initial conditions and historical experience in shaping a country's financial services trade strategy; thirdly, the scheduling approach of the (typically self-contained) financial services chapter which both contributes to, and is determined by, the willingness to liberalize; and finally the authorities should be cognizant of important nuances between the two main negotiating templates.